Surface Modifications of Zirconia Dental Implant for Improving Osseointegration - Adil Othman Abdullah; Saya Hadi Raouf (Zanco Journal of Pure and Applied Sciences, 2024)
The aim of the current review is focused on compiling a comprehensive overview of the zirconia surface modification for implant interface osseointegration. Background: The importance of osseointegration for patients has notably gained importance and been accompanied by a dramatic increase in the number of relevant products and procedures over several decades, with a concomitant rise in publications on this topic. An electronic search was conducted across Ovid Medline, complemented by a manual search across individual databases, such as Cochrane, Web of Science databases, and Google Scholar for the purpose of literature analysis on the mentioned topic. The studies were reviewed and compared. This article summarizes the current scientific and clinical opinions through a brief review with regards to the preferred way of zirconia surface treatment and its impact on osseointegration. There are controversies in terms of performing zirconia surface treatment. Surface bio-inertness of zirconia implants result in limited osseointegration compared to titanium implants.